Breviscapine Pretreatment Inhibits Myocardial Inflammation and Apoptosis in Rats After Coronary Microembolization by Activating the PI3K/Akt/GSK-3β Signaling Pathway - Chen ZQ; Zhou Y; Chen F; Huang JW; Zheng J; Li HL; Li T; Li L (Dove Medical Press, 2021)
Zhi-Qing Chen,1 You Zhou,1 Feng Chen,2 Jun-Wen Huang,1 Jing Zheng,1 Hao-Liang Li,1 Tao Li,1 Lang Li1 1Department of Cardiology, The First Affiliated Hospital of Guangxi Medical University & Guangxi Key Laboratory Base of Precision Medicine in Cardio-Cerebrovascular Diseases Control and Prevention & Guangxi Clinical Research Center for Cardio-Cerebrovascular Diseases, Nanning, People’s Republic of China; 2Department of Emergency, The First Affiliated Hospital of Guangxi Medical University, Nanning, People’s Republic of ChinaCorrespondence: Lang LiDepartment of Cardiology, The First Affiliated Hospital of Guangxi Medical University & Guangxi Key Laboratory Base of Precision Medicine in Cardio-Cerebrovascular Diseases Control and Prevention & Guangxi Clinical Research Center for Cardio-Cerebrovascular Diseases, 6 Shuangyong Road, Nanning, 530021, Guangxi, People’s Republic of ChinaTel/Fax +86-771-5331171Email drlilang99@126.comPurpose: Coronary microembolization (CME) can cause myocardial inflammation, apoptosis and progressive cardiac dysfunction. On the other hand, breviscapine exerts a significant cardioprotective effect in many cardiac diseases although its role and the potential mechanisms in CME remain unclear. Therefore, the present study aimed to ascertain whether pretreatment with breviscapine could improve CME-induced myocardial injury by alleviating myocardial inflammation and apoptosis. The possible underlying mechanisms were also explored.Methods: In this study, 48 Sprague-Dawley (SD) rats were randomly assigned to the CME, CME + breviscapine (CME + BE), CME + breviscapine + LY294002 (CME + BE + LY) and sham groups (12 rats per group). In addition, the CME model was successfully established by injecting 42 μm inert plastic microspheres into the left ventricle of rats. Rats in the CME + BE and CME + BE + LY groups received 40 mg/kg/d of breviscapine for 7 days before inducing CME. Moreover, rats in the CME + BE + LY group were intraperitoneally injected with the phosphoinositide 3-kinase (PI3K) specific inhibitor, LY294002 (10 mg/kg) 30 minutes before CME modeling. 12 h after surgery, the study measured cardiac function, the serum levels of markers of myocardial injury, myocardial inflammation-associated mRNAs and proteins, myocardial apoptosis-associated mRNAs and proteins and conducted myocardial histopathology.Results: The findings demonstrated that pretreatment with breviscapine alleviated myocardial injury following CME by improving cardiac dysfunction, decreasing the serum levels of markers of myocardial injury, reducing the size of myocardial microinfarct and lowering the cardiomyocyte apoptotic index. More importantly, pretreatment with breviscapine resulted to a decrease in the levels of inflammatory and pro-apoptotic mRNAs and proteins in myocardial tissues and there was an increase in the levels of anti-apoptotic mRNAs and proteins. However, these protective effects were eliminated when breviscapine was combined with LY294002.Conclusion: The findings from this study indicated that breviscapine may inhibit myocardial inflammation and apoptosis by regulating the PI3K/protein kinase B (Akt)/glycogen synthase kinase-3β (GSK-3β) pathway, thereby ameliorating CME-induced cardiac dysfunction and reducing myocardial injury.Keywords: breviscapine, coronary microembolization, PI3K/Akt/GSK-3β, myocardial inflammation, apoptosis